Five Holistic Learning Approaches in Educating Students' Emotional and Spiritual Intelligence in Junior High School - Dwietama, Regita Ayu; Suresman, Edi; Firmansyah, Mokh. Iman (International Journal of Multidisciplinary Research of Higher Education, 2024)
This study aims to analyze applying a holistic approach to learning Islamic religious education to improve emotional and spiritual intelligence in junior high school students. This study uses a qualitative method with a case study type. The data source is collected from six informants through purposive sampling. The data is collected through interviews and observations and analyzed using the Milles and Huberman analysis techniques. The results showed five main themes that support the development of students' emotional and spiritual intelligence: i) the integration of Islamic values in Islamic religious education learning plays a vital role in shaping the character and management of students' emotions. ii) learning based on worship practices increases students' closeness to the spiritual aspects of their lives. iii) contextual approach in Islamic religious education learning optimizes students' social and emotional awareness through direct connection with their social situations. iv) the habituation of Islamic manners and values in students' daily lives strengthens their ability to manage emotions positively. v) the role of Islamic religious education teachers as role models is very influential in developing students' emotional and spiritual intelligence. This research provides insights into how a holistic approach to Islamic religious education learning can improve students' emotional and spiritual qualities, further contributing to their character development and overall well-being.